Konservasi Lingkungan Kawasan Borobudur dengan Manajemen Berbasis pada Pembangunan Masyarakat Lokal - Amiluhur Soeroso (Economic Journal of Emerging Markets, 2009)
This research aims to seek expressive of level community toward living environment attributes that support the holistic conservation management of Borobudur area. Data were obtained from local community with structured questionnaire and conducted by using both factor and cluster analysis. The results indicate that community of Borobudur is in participation level. Besides that, their views which attributes of bio-geophysics are natural conservation and energy saving; economy attributes are tourism synergy and partnership, while attributes of socio-culture are safeguarding cultural identity and art performance of community. For the reason, the survival of Borobudur’s site in the future will fully depend on its sustainable development policy to those attributes. Management of Borobudur should have not to focus on sites, material or artifacts and shifting to space or area where human being is living.